Foreign Workers and Law Enforcement in Japan. - Herbert, Wolfgang (Taylor & Francis, 2010)
This is a detailed study of the extent to which an increased influx of foreign workers is a threat to law and order in the context of the data-generating process of police statistics and the media coverage of "crimes" committed by foreigners. It shows that a general mood in which foreign workers are viewed as potential danger to Japanese society "protects" the criminalization of foreign "illegal" migrant workers